Zhong Dang Pan and Gerald M. Kosicki Framing Model Analysis on Citayam Fashion Week News in Tempo.co and Tirto.id Online Media - Rizky Pratama; M. Yoserizal Saragih (PT Mattawang Mediatama Solution, 2022)
The goal of this research was to determine the analysis of online media framing Tempo.co and Tirto.id regarding Citayam Fashion Week news. In addressing these issues, the author employs a constructivist approach, which views discourse as a result of the construction of social reality. This research is classified as library research, with data collected by citing and analyzing representative literature with relevance to the problems discussed, followed by reviewing and concluding. Following a discussion of framing analysis of Citayam Fashion Week news using the Zhongdang Pan and Gerald framing method. M. Kosicki. The author discovered that, in terms of framing devices (Syntax, Script, Thematic, and Rhetorical), Tempo.co in constructing social reality, particularly news about Citayam Fashion Week, was quite neutral in presenting news based on information obtained from sources, whereas online media Tirto was quite aggressive. id is quite positive in its coverage of Citayam Fashion Week, presenting and emphasizing all of the informants' opinions.